Paper - Jerzy F. Latka (A+BE: Architecture and the Built Environment, 2018)
Paper is a material we know from our day-to-day lives because it is used in newspapers, tissues, packaging, etc. Its web-like structure consists of wood fibres and can be visualised by comparing it to the cooking of a portion of spaghetti that is later served onto a plate.